(untitled) (Research, Society and Development, 2021)
Objective: To present a review of current literature on methods of approaching nursing care in the diagnosis of gastroschisis, focusing on nursing care for pregnant women and pre, trans and postoperative care, addressing the main nursing diagnoses to be used in the period perioperative period in the mother-infant binomial. Methodology: This is an integrative descriptive review with a qualitative approach, through the analysis of articles related to care for pregnant women diagnosed with fetal gastroschisis associated with Nursing Care to the neonate in the operating room, comprising 25 articles, with 10 articles being selected among 2017-2020 to compose the table and the descriptors were used: Gastroschisis, Nursing Care, Surgical Center and Newborn. Results: There is a shortage and deficiency in primary care regarding the early diagnosis of gastroschisis, lack of adequate psychosocial support for the mother and family, and this in its entirety in the gestational and perioperative period. Among the main functions of nurses in the perioperative period, the following stand out: parental authorization for the surgical procedure, monitoring of vital signs, surgical checklist, handling the NB in a heated crib, organizing material for possible resuscitation; provide information and clarify doubts to parents, it is important to emphasize that every procedure performed must be registered in the medical record. Conclusion: It is necessary to develop a specific care mode as a nursing care protocol that involves conducts and care from the perioperative period to possible hospital discharge; more in-depth studies should be carried out with the purpose of qualifying and training the multidisciplinary team to ensure assistance free from avoidable errors.